2007
DOI: 10.1128/cvi.00480-06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Enzyme Immunoassay for Detection of Immunoglobulin M Antibodies to West Nile Virus and the Importance of Background Subtraction in Detecting Nonspecific Reactivity

Abstract: Since the introduction of West Nile virus (WNV) in the United

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…9 When we began this study in 2003, we used the only nationally accepted protocol for determination of IgM and IgG antibodies at that time, which was based on the CDC recommendations and previously published studies. With the introduction of Food and Drug Administration (FDA)-approved commercially available kits through Focus Diagnostics and PanBio, Inc. a couple of years into the study, 10 we made the decision to continue to use the CDC protocol to remain consistent with methods and interpretations. In 2010, we began to use the commercially available kits by PanBio.…”
Section: Discussionmentioning
confidence: 99%
“…9 When we began this study in 2003, we used the only nationally accepted protocol for determination of IgM and IgG antibodies at that time, which was based on the CDC recommendations and previously published studies. With the introduction of Food and Drug Administration (FDA)-approved commercially available kits through Focus Diagnostics and PanBio, Inc. a couple of years into the study, 10 we made the decision to continue to use the CDC protocol to remain consistent with methods and interpretations. In 2010, we began to use the commercially available kits by PanBio.…”
Section: Discussionmentioning
confidence: 99%
“…Most WNV IgM assays utilize recombinant premembrane/envelope (preM/E) protein (Davis et al, 2001). These assays exhibit excellent sensitivity for identifying individuals recently exposed to WNV (Hogrefe et al, 2004;Muerhoff et al, 2004;Holmes et al, 2005;Tilley et al, 2005;Rawlins et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, despite the existence of highly sensitive tests, such as ELISA and immuno-blotting techniques, inconclusive serological results are quite frequent in infectious diseases, such as Chagas disease, tuberculosis, leprosy, and West Nile virus [74]. Recently, it was reported that serum samples from patients with myco-bacterial infections ( Mycobacterium leprae ) crossreact with HIV structural proteins Gp41, p55, and p18 [75].…”
Section: Comparison Of Elisa and Iacementioning
confidence: 99%